2022
DOI: 10.29100/jipi.v7i1.2410
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Metode Residual Network (Resnet) Dalam Klasifikasi Penyakit Pada Daun Gandum

Abstract: 2) ABSTRAK Gandum adalah jenis tanaman yang kaya karbohidrat. Permintaan gandum di Indonesia selalu meningkat setiap tahun tetapi berbanding terbalik dengan jumlah produksi gandum nasional. Salah satu faktor yang menghambat produksi gandum adalah kegagalan panen akibat penyakit atau hama. Penyakit yang umum pada tanaman gandum adalah Septoria dan Stripe Rust. Penyakit tersebut dapat diidentifikasi melalui warna dan bercak daun. Seiring perkembangan teknologi, petani dapat mengawasi tanaman secara otomatis meng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
0
6
0
7
Order By: Relevance
“…Several studies have also proven the excellence of this architecture of CNN as reported in the research [10] on the classification of diseases attacking wheat leaves. The best scenario discussed in the research was related to the 80:20 ratio, with the data consisting of 232 training data and 59 test data by using the architecture of ResNet 152V2.…”
Section: Introductionmentioning
confidence: 77%
“…Several studies have also proven the excellence of this architecture of CNN as reported in the research [10] on the classification of diseases attacking wheat leaves. The best scenario discussed in the research was related to the 80:20 ratio, with the data consisting of 232 training data and 59 test data by using the architecture of ResNet 152V2.…”
Section: Introductionmentioning
confidence: 77%
“…(13) Precision indicates a correctly classified prediction of positive values divided across positive classified data [28]. (14) Recall shows the comparison of the positive correct predicted value with the entire positive correct value [29]. (15) The F1-Score shows the average comparison of precision and recall values [29].…”
Section: ) Kernel Radial Basic Function (Rbf)mentioning
confidence: 99%
“…(14) Recall shows the comparison of the positive correct predicted value with the entire positive correct value [29]. (15) The F1-Score shows the average comparison of precision and recall values [29]. ( 16)…”
Section: ) Kernel Radial Basic Function (Rbf)mentioning
confidence: 99%
“…(13) Precision indicates a correctly classified prediction of positive values divided across positive classified data [28]. (14) Recall compares the positive correct predicted value with the entire positive correct value [29]. (15) The F1-Score shows the average comparison of precision and recall values [29].…”
Section: C) Kernel Radial Basic Function (Rbf)mentioning
confidence: 99%
“…(14) Recall compares the positive correct predicted value with the entire positive correct value [29]. (15) The F1-Score shows the average comparison of precision and recall values [29]. ( 16)…”
Section: C) Kernel Radial Basic Function (Rbf)mentioning
confidence: 99%